2013
DOI: 10.1111/sji.12020
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 Gene Promoter and NFKB1 Promoter Insertion/Deletion Polymorphisms in Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is a connective tissue disease characterized by fibrotic, immunological and vascular abnormalities. Nuclear factor-kB (NFKB), as a key transcription factor involved in the regulation of immune responses, appears to be a good candidate for studies on the pathogenesis of autoimmune diseases, as well as the interleukin-10 (IL-10) polymorphism, which other studies have suggested an association with SSc. Our objective was to study the association of NFKB and IL-10 gene polymorphisms with SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Moreover, it has been shown to induce pro- and anti-inflammatory responses 55. The genetic variants -1082A/G, -819C/T, and 592A/C in the promoter region of the IL-10 gene have been described frequently in association with cutaneous diseases, while their influence on IL-10 production is unclear 58-61. A genetic association of -819T>C in IL-10 with AIU, including both AIAU and AICU, was identified in a Korean population 62.…”
Section: The Candidate Gene Approach In Cumentioning
confidence: 99%
“…Moreover, it has been shown to induce pro- and anti-inflammatory responses 55. The genetic variants -1082A/G, -819C/T, and 592A/C in the promoter region of the IL-10 gene have been described frequently in association with cutaneous diseases, while their influence on IL-10 production is unclear 58-61. A genetic association of -819T>C in IL-10 with AIU, including both AIAU and AICU, was identified in a Korean population 62.…”
Section: The Candidate Gene Approach In Cumentioning
confidence: 99%
“…The mechanism behind NF-κB1 in relation to disease susceptibility remains unclear although -94 del ATTG has been proven to reduce activation of NF-κB1 transcription. A meta-analysis suggests an association between NF-κB1 -94ins/delATTG promoter polymorphism to certain autoimmune and inflammatory disease (diabetes mellitus, ulcerative colitis and psoriasis) in Asian population but not in the Caucasian population (6,27). However, only one study suggested significant association of the homozygous mutation genotype del/del with the occurrence of aggressive periodontitis in a cohort of German Caucasians (7).…”
Section: Genotypes and Alleles Distribution Of Polymorphisms In The Nmentioning
confidence: 99%
“…Five members of the NF-κB family have been identified, and they are NF-κB1 (p105/p50), NF-κB2 (p100/p52), RelA (p65), RelB and c-Rel. Several polymorphisms have been identified in the promoter region of NF-κB1 gene, which is insertion/deletion (-94ins/delATTG) (6). However, one study conducted on periodontal disease reported that del/del genotype of NF-κB1 gene was associated with aggressive periodontitis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies with animal models and cell culture systems indicate the interplay between NF- κ B and lung carcinogenesis, which emphasizes the importance of targeting the NF- κ B signaling pathway for lung cancer treatment and chemoprevention [7]. NF- κ B, a nuclear transcription factor [8], was first identified in 1986 by Sen and Baltimore [9]. It was initially observed to be a transcription factor binding to the intronic enhancer of the kappa light chain gene (the κ B site) in B cells, but it was later shown to be present in every cell type [10].…”
Section: Introductionmentioning
confidence: 99%